Peran Service Excellent dalam Meningkatkan Loyalitas Konsumen : Studi Kasus UMKM RM Kamang Jaya Kota Medan - Juwita Novitasari Simorangkir; Mishul Jayana; Nesa Einge Regina Br. Tarigan; Elga Gresia Br. Surbakti; Lionanda Maretcha Marpaung; Dionisius Sihombing; Fadli Agus Triansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to explore the role of service excellence in enhancing consumer loyalty in culinary MSMEs, with a case study at RM Kamang Jaya in Medan City. In facing intense competition in the food industry, excellent service becomes an important strategy to maintain and expand the customer base. A qualitative approach with a case study method was employed to deeply examine customer experiences, perceptions, and service practices through interviews, observations, and documentation. The findings show that the consistent application of service standards, friendly attitudes of staff, and attention to detail in service delivery greatly contribute to customer satisfaction and loyalty. Good service has been proven to encourage repeat orders, create positive experiences, and enhance word-of-mouth promotion. Despite some technical obstacles, such as order errors or menu limitations, the quick response and professional attitude of employees were able to minimize their impact. These findings confirm that service excellence not only meets the functional needs of consumers but also builds emotional attachment, which becomes the foundation of long-term loyalty. The implications of this research are significant for other MSME actors in designing superior service strategies to face increasingly complex business competition.